Biomimetic Materials Synthesis from Ferritin-Related, Cage-Shaped Proteins - Ceci, Pierpaolo; Morea, Veronica; Fornara, Manuela; Bellapadrona, Giuliano; Falvo, Elisabetta; Ilari, Andrea (IntechOpen, 2012)
None